Spiritual Leadership and Meaningful Work: Implications for Employee Engagement and Organizational Citizenship Behavior - Wijil Nugroho; Ririsma Sihombing (JURNAL ECONOMINA, 2026)
Leadership research increasingly recognizes meaning, values, and connectedness as critical sources of positive employee behavior. This article develops a conceptual framework explaining the relationships among spiritual leadership, meaningful work, work engagement, and organizational citizenship behavior (OCB). Drawing on organizational behavior literature, spiritual leadership is positioned as a leadership approach that cultivates shared vision, hope/faith, altruistic love, calling, and membership. Meaningful work is proposed as the psychological mechanism translating spiritual leadership into work engagement, whereas engagement is conceptualized as the cognitive, emotional, and physical energy that enables extra-role behavior. The framework offers seven propositions for future empirical testing, including a serial mediation path from spiritual leadership to meaningful work, engagement, and OCB. The article contributes by integrating spiritual leadership theory, meaningful work, psychological conditions of engagement, job demands-resources theory, and social exchange theory into a parsimonious organizational behavior model. It also provides practical implications for leadership development, meaningful job design, and organizational cultures that foster citizenship behavior.